2018
DOI: 10.1021/acs.jpclett.8b02474
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Prestress-Driven Optical Modulations of Flexible ZnO Thin Films Processed in Stretching Mode

Abstract: Experimental verification of optical modulation with external stress has not been easily available in flexible systems. Here, we intentionally induced extra stress in wide band gap ZnO thin films by a unique prestress-driven deposition processing that utilizes a stretching mode. The stretching mode provides homogeneous but biaxial stresses in the hexagonal wurtzite structure, leading to the extension of the c-axis and the contraction of the a-axis. As a result, the reduction of the optical band gap by ∼150 meV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 37 publications
3
17
1
Order By: Relevance
“…We find that the impact of η on the band gap of ZnO thin films is practically negligible (at least in comparison to the CeO 2 and TiO 2 cases), which is consistent with previous experimental observations [16]. For instance, according to our first-principles calculations, E g for the wurtzite phase increases by just 2% at η = +5% and decreases by 3% at η = −5%; in comparison, a reduction of 4% was obtained at η ≈ −5% in experimental work [16]. Meanwhile, the band gap for the zinc-blende phase is changed by even smaller amounts, with only a 0.5% reduction at η = +7% and a 0.5% increase at η = −7% (note the opposite sign in the strain-driven E g change as compared to the wurtzite case, Fig.5d).…”
Section: Zinc-blende and Wurtzite Zno (001)supporting
confidence: 92%
See 3 more Smart Citations
“…We find that the impact of η on the band gap of ZnO thin films is practically negligible (at least in comparison to the CeO 2 and TiO 2 cases), which is consistent with previous experimental observations [16]. For instance, according to our first-principles calculations, E g for the wurtzite phase increases by just 2% at η = +5% and decreases by 3% at η = −5%; in comparison, a reduction of 4% was obtained at η ≈ −5% in experimental work [16]. Meanwhile, the band gap for the zinc-blende phase is changed by even smaller amounts, with only a 0.5% reduction at η = +7% and a 0.5% increase at η = −7% (note the opposite sign in the strain-driven E g change as compared to the wurtzite case, Fig.5d).…”
Section: Zinc-blende and Wurtzite Zno (001)supporting
confidence: 92%
“…Both compressive (η < 0) and tensile (η > 0) biaxial strains ranging from zero up to a maximum absolute value of 7% have been considered in the simulations. These values are comparable in magnitude to the η's achieved experimentally in the same materials [14][15][16]. At the end of this section, we introduce a simple analytical model that depends only on structural and dielectric susceptibility changes and reproduces qualitatively, and helps in understanding, the general band gap trends induced by η.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…It has been reported that the bandgap narrowing of piezoelectric ZnO is induced under a tensile strain along the c-axis by the respective downward and upward shifts of the CB and the VB. [71,72] Thus, this red-shift in the UV peak position was possibly due to the inhomogenous band bending at the AuNI/ZNT interface due to the laser-induced AuNI reconstruction and the resulting applied tensile strain. Some concerns may be raised regarding the impact of laser exposure on the PL measurement in the UV range because the laser irradiation can produce defect states in ZnO.…”
Section: In Situ Photothermal Surface Restructuring/melting Behavior In the Auni-znts Hybrid: Desorption And Ionizationmentioning
confidence: 98%